2018
DOI: 10.1371/journal.pone.0208715
|View full text |Cite
|
Sign up to set email alerts
|

An increase in mean platelet volume during admission can predict the prognoses of patients with pneumonia in the intensive care unit: A retrospective study

Abstract: Platelets play an important role in hemostasis, inflammation, and immunity. Mean platelet volume (MPV), considered a marker of platelet function and activation, is associated with increased morbidity and mortality in sepsis, coronary artery disease, and chronic inflammatory disease. However, the clinical characteristics and prognostic significance of MPV changes for patients with pneumonia in the intensive care unit (ICU) have not been investigated. This retrospective study was conducted using data from an ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 30 publications
(26 reference statements)
0
34
4
Order By: Relevance
“…Larger platelets usually contain more secretory granules, more RNA, and thus become more reactive than their smaller counterparts [39]. Although SELP expression did not significantly correlate with the outcome of sepsis in these patients, increased MPV values also predicted disease prognosis, as reported by others in sepsis with pneumonia [40]. In the presence of an augmented mRNA level that predicts changes in protein expression, higher P-selectin concentration was detected in platelet lysates after 72 h of sepsis onset that could be a result of altered miRNA and mRNA levels in platelets and MKs.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Larger platelets usually contain more secretory granules, more RNA, and thus become more reactive than their smaller counterparts [39]. Although SELP expression did not significantly correlate with the outcome of sepsis in these patients, increased MPV values also predicted disease prognosis, as reported by others in sepsis with pneumonia [40]. In the presence of an augmented mRNA level that predicts changes in protein expression, higher P-selectin concentration was detected in platelet lysates after 72 h of sepsis onset that could be a result of altered miRNA and mRNA levels in platelets and MKs.…”
Section: Discussionmentioning
confidence: 45%
“…To examine the contribution of calpain substrate Dicer enzyme in the generation of altered miRNA levels in sepsis, we applied a MK model for sepsis-induced Dicer dysfunction in which 0.3 × 10 6 /mL MEG-01 cells were treated by a specific exogenous calpain 1 and 2 inhibitor, calpeptin (40 µmol/L, Sigma-Aldrich, St. Louis, MO, USA) for 24 h in a similar way as it was performed previously [21,40]. The effect of calpeptin on miRNA expression was assessed in the following settings: vehicle (DMSO); LPS or TNF-α; LPS or TNF-α, together with calpeptin; calpeptin alone as a positive control.…”
Section: Analysis Of Dicer Function On Mirna Level Through Calpain Inmentioning
confidence: 99%
“…However, the evidence in pneumonia now is limited and controversial. Two studies showed that increasing MPV may be linked to poor outcomes [11,12], whereas one study conversely showed a decrease [13]. Besides, there is an important difference in platelet biology impacted by sex.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al 4 indicated that MPV measurements may be used as a prognostic marker of mortality in intensive care unit patients with pneumonia.…”
Section: To the Editormentioning
confidence: 99%